Effects of a music therapy and music listening intervention for nursing home residents with dementia: a randomized controlled trial - Prick, Anna-Eva J. C.; Zuidema, Sytse U.; van Domburg, Peter; Verboon, Peter; Vink, Annemieke C.; Schols, Jos M. G. A.; van Hooren, Susan (Frontiers in Medicine, 2024)
Introduction The aim of the present study was to evaluate the effects of an individual music therapy intervention and an individual music listening intervention on neuropsychiatric symptoms and quality of life in people with dementia living in a nursing home and on professional caregiver’s burden to be able to make statements about their specific value of application in clinical practice. Methods A multicenter single blind randomized controlled trial with three groups was performed: an individual music therapy intervention (IMTI) group (n = 49), an individual music listening intervention (IMLI) group (n = 56) and a control group (n = 53) receiving usual care. The interventions were given during three weeks, three times a week on non-consecutive days during 30–45 minutes for in total nine sessions. The endpoint of the study is the difference from baseline to interim (1,5 week), post-intervention (3 weeks) and follow-up (6 weeks) in reported scores of problem behaviour (NPI-NH) and quality of life (Qualidem) in people with dementia and occupational disruptiveness (NPI-NH) in care professionals. Results In total 158 people with dementia were randomized to one of the two intervention groups or the control group. Multilevel analyses demonstrated that hyperactive behaviour assessed by the NPI-NH was significantly more reduced for the IMLI group at follow up and that restless behaviour assessed by the Qualidem was significantly more reduced for the IMTI group at post and follow-up measurement compared to the control group. No significant effects between groups were found in other NPI-NH clusters or Qualidem subscales. Conclusion In conclusion, because we found no convincing evidence that the IMTI or IMLI is more effective than the other both interventions should be considered in clinical practice. For the future, we advise further research into the sustainability of the effects with alternative designs, like a single case experimental design.